Hubungan antara iklim keselamatan dengan prestasi keselamatan pekerjaan : Kajian di ILJTM Lembah Klang - Muhamad Aidil, Harun (2014)
This study is intended to determine and examine the relationship between safety climate and safety performance of work in ILJTM Klang Valley. Five dimensions of safety climate in this study are safety attitude, employee involvement, employee safety commitment, co-worker safety and risk perception. To achieve the objectives of the study, a total of 140 sets of questionnaires were distributed to the operational department staffs in ILJTM Klang Valley. Quantitative data were analyzed using SPSS software. It includes Descriptive Statistics Analysis, Reliability Test and Pearson Correlation Test. In addition, Multiple Regression Test is used to test the hypotheses. Pearson Correlation Test found that there is a positive relationship between almost all safety climate dimensions and safety performance and its components. Whereas, Multiple Regression Test showed that employee safety commitment and risk perception are significantly related to safety performance and its components. Meanwhile, only employee involvement and co-worker safety have a significant relationship with safety participation. Other safety climate dimension namely safety attitude was not significantly related to safety performance and its components. Finally, the implications of this study and directions for future research were discussed.